1997
DOI: 10.1148/radiology.203.2.9114109
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between plaque mass and neointimal hyperplasia after stent placement in Yucatan micropigs.

Abstract: The amount of plaque present before stent placement was a determinant of the amount of intimal hyperplasia present after stent placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
0
10
1
Order By: Relevance
“…6,7 However, previous studies only report on the relationship between cross-sectional area of the plaque burden and cross-sectional area of the neointima formation. 6,7 No data exist as to whether the asymmetries in neointimal formation may be explained by the eccentricity of the persistent plaque burden. This subject warrants further study because in eccentric lesions, a confounding factor, such as progression of atherosclerosis at the low SS 21 side, may be present.…”
Section: Relation Between Ss and Thmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 However, previous studies only report on the relationship between cross-sectional area of the plaque burden and cross-sectional area of the neointima formation. 6,7 No data exist as to whether the asymmetries in neointimal formation may be explained by the eccentricity of the persistent plaque burden. This subject warrants further study because in eccentric lesions, a confounding factor, such as progression of atherosclerosis at the low SS 21 side, may be present.…”
Section: Relation Between Ss and Thmentioning
confidence: 99%
“…3 A number of risk factors, such as thrombus formation 4 and endothelial dysfunction, 5 are related to restenosis, but their relationship with a specific intima hyperplasia distribution is unknown. Localizing factors that have been studied include plaque burden 6,7 and wall stress. 8 In the present study, we focus on the role of shear stress (SS).…”
mentioning
confidence: 99%
“…shown that this regimen results in a sustained tenfold We developed an atherosclerotic model in the Yucatan increase in the total cholesterol level to 14.9 (61.3) micropig [7] that meets most of these conditions. We found mmol / l, and an approximately 3.5-fold increase in the that the morphology of the atherosclerotic plaque covers high-density lipoprotein (HDL) level to 2.2 (60.1) mmol / the whole range from hypercellular fibromuscular plaque l. After discontinuation of the atherogenic diet, the levels to lipid lakes that are covered by a fibrous cap and of cholesterol and HDL cholesterol dropped to base levels complex lesions with calcification, cholesterol clefts and (1.560.2 and 0.660.1 mmol / l, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…High-fat, high-cholesterol, and high-sugar diets have been shown to induce hyperlipidemia, obesity, and insulin resistance in humans and rodents [20][21][22]. Dietary-induced hyperlipidemia pig models have also been established [23][24][25][26][27][28][29].…”
Section: Gene Expression Profiles Change Related To Hyperlipidemiamentioning
confidence: 99%